Climate Change Mitigation and Disaster Preparedness in Indonesia’s Outermost Islands - Nouldy Jan Tangka; Rido Hermawan; Kup Yanto Setiyono; Andrea S. Pulungan Pulungan (Jurnal Lemhannas RI, 2025)
Purpose: This study examines how climate change mitigation shapes disaster preparedness in Indonesia's outermost islands and strengthens national resilience in response to escalating climate risks and the strategic challenges facing border regions. Study Design/Methodology/Approach: This study adopts a qualitative descriptive case study supported by policy analysis, document analysis, and SWOT analysis. National legislation, government reports, official statistics, and international publications are analysed to evaluate institutional capacity, governance, and climate adaptation measures. The Asta Gatra-based National Resilience framework provides the analytical lens for examining the relationships between climate change mitigation, disaster preparedness, and regional resilience. Findings: Climate change mitigation on Miangas Island remains fragmented because institutional coordination, early warning systems, disaster infrastructure, and local adaptive capacity have not developed in line with increasing climate pressures. A SWOT analysis identifies community social capital, strategic border status, national policy support, and multi-stakeholder collaboration as key strengths for strengthening disaster preparedness through adaptive governance, institutional integration, and community-based mitigation within the Asta Gatra-based National Resilience framework. Originality/Value: The study extends climate change mitigation literature by integrating social-ecological systems theory, disaster risk reduction, adaptive governance, and the Asta Gatra-based National Resilience framework into a unified analytical perspective that explains how climate mitigation strengthens disaster preparedness and reinforces resilience across Indonesia's outermost border islands.